Molecular mechanics: theoretical basis, rules, scope and limits - Boeyens, Jan C. A.; Comba, Peter (Coordination chemistry reviews, 2001)
Molecular mechanics is a simple model, and it is based on a classical parameterization of non-classical effects for the computation of molecular structure. The basic concept of force field calculations is discussed and, based on the theoretical frame, the emerging scope and limits of the approach, and rules for the application, interpretation of the results and their communication are presented.